Le clocher et l’empire : tensions et contradictions de la patria criolla dans la vice-royauté de Lima au XVIIe siècle - Bernard Lavallé (Centre de Recherches sur les Mondes Américains, 2010)
The present article shows how Creole patriotism asserted itself in two different ways, depending on whether it emerged from the American conflict between Hispanics and Creoles, or from Spain, in response to disparagement. The former kind was localist, extolled the patria chica and left out wider geographical references - including conceptual ones - which some regions then seemed to be lacking. The latter kind was likely to rest upon solidarity and dawning continental identity against Europeans criticisms and contempt.